Pengaruh Pemberian D-Galaktosa Intraperitoneal terhadap Kadar IL-6 pada Tikus Sprague-Dawley - Manus, Widya Christine; Pratiwi, Johana Puspasari Dwi; Ardiyan, Yustina Nuke (Bioscientist : Jurnal Ilmiah Biologi, 2023)
As humans age, there is a decline in the function and physiological mechanisms of the body, which can affect quality of life. Chronic inflammation is one of the characteristics found in the aging process, marked by an increase in proinflammatory cytokines in circulation. IL-6 is one of the cytokines that play a role in chronic inflammation. This study aimed to determine serum IL-6 levels using D-galactose induction in Sprague-Dawley rats. The study used a pure experiment with a post-test only control group design, in which 36 male Sprague-Dawley rats were divided into two groups: control and treatment. The research sample was serum, and the control group received a placebo of 0.9% NaCl at a dose of 400 mg/day/kg intraperitoneally. The treatment group, which underwent aging induction, was given D-galactose at the same dose and route. The treatment was administered for 6 weeks, and serum was collected from blood taken in the 6th week. The results indicated that the administration of D-galactose did not have a significant effect on increasing IL-6 levels.